Community-based monitoring: shoreline change in Southwest Alaska - Christian, Jessica E.; Buzard, Richard M.; Spellman, Katie L.; Baldwin, Harper L.; Bogardus, Reyce C.; Carlson, Jeanette; Dunham, Gabe; Flensburg, Susan; Glenn, Roberta J. T.; Overbeck, Jacquelyn R.; Maio, Chris V. (Frontiers in Climate, 2025)
Arctic amplification of climate change has resulted in increased coastal hazards impacts to remote rural coastal communities in Alaska where conducting research can be difficult, requiring alternate methods for measuring change. The pilot program, Stakes for Stakeholders, was initially planned to be funded from 2016–2018. Upon project completion the work has shifted to individual community’s partnering with several agencies to continue the work. This research showcases a successful long-term community-based erosion monitoring program in two rural communities in Southwest Alaska. The resulting outputs from the workflow we developed were (1) locally prioritized data products, such as a hazard assessment report for Chignik Bay and (2) evaluation rubrics used to assess the suitability of future sites and the efficacy of the program. Our model of two-way communication, responsiveness to individual community needs, and attention to efficiency and effectiveness of the program workflow, can serve as a model for universities, for-profit, non-profit, Tribal, city, state, and federal research agencies and communities partnering to respond to global climate change.